(untitled) (Res Gesta, 2025)
The transformation processes in the port sectors show the need to explore strategies to preserve their unique heritage. The ports determined peculiar adjacent sites that were configured around their activity and formed spaces with socio-cultural, architectural and urban characteristics that deserve special appreciation. The conception of areas of heritage value is recognized as a possible and practiced strategy to advance in the protection of the tangible and intangible assets that characterize this type of sector. However, there are few studies and actions related to the delimitation of urban-port areas. The Port neighborhood of Mar del Plata presents distinctive features to undertake this approach, in a framework of relevant dynamics of changes together with the absence of specific protections. Therefore, by means of a qualitative methodology, the investigation of written and graphic sources together with in situ surveys, progress is made in the definition of fragments of interest through the analysis of socio-historical and material variables, in order to progress in appropriate protections.